(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Today, the global goal of mastering a foreign language is the opportunity to participate in the dialogue of cultures. The article discusses the features of teaching a foreign language to students of technical universities; organization of foreign language teaching in a functional context, basic principles of teaching English as a foreign language.